Jonathan Allen, ed., Lost Envoy: The Tarot Deck of Austin Osman Spare (London: Strange Attractor Press, 2016), 336 pp, £35 (cloth). - Cusack, Carole M. (Pomegranate, 2018)
Jonathan Allen, ed., Lost Envoy: The Tarot Deck of Austin Osman Spare (London: Strange Attractor Press, 2016), 336 pp, £35 (cloth).